2000
DOI: 10.1524/ract.2000.88.6.361
|View full text |Cite
|
Sign up to set email alerts
|

Removal of234,238U,226Ra,210Po and210Pb from drinking water by ion exchange

Abstract: Six organic and five inorganic ion exchangers were studied for the removal of natural radionuclides from drinking water. In the first phase, distribution coefficients (K D ) of uranium and radium were determined in three model solutions: a good quality water, an FeϪMn-rich water and a saline water simulant. The exchangers showing highest K D 's for U and Ra were tested in column mode experiments for the removal of U, 226 Ra, 210 Po and 210 Pb from a real ground water. Considering the total 1800 processed bed v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 11 publications
0
22
0
2
Order By: Relevance
“…where C 0 and C are the uranium concentration in solution before and after contact; V the solution volume (mL) and m is the dry resin mass (g) [13,14,17].…”
Section: Batch Adsorption Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…where C 0 and C are the uranium concentration in solution before and after contact; V the solution volume (mL) and m is the dry resin mass (g) [13,14,17].…”
Section: Batch Adsorption Experimentsmentioning
confidence: 99%
“…The majority of the studies for uranium removal are based on the presence of species like UO 2 (CO 3 ) 2 2− and UO 2 (CO 3 ) 3 4− in groundwater. In acid mine drainage, where stable anionic uranium complex is mainly present as UO 2 (SO 4 ) 3 4− , the literature is scarce [5,[13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical separation commonly employs ion-exchange and chelating resins [3,4,5,6]. The choice of the best operational conditions for sorption and elution of metal ions is a problem mostly dealt with on a purely experimental basis, while they could be usefully predicted if sorption equilibria were known.…”
Section: Introductionmentioning
confidence: 99%
“…The other resin, chelating aminophosphonate resin, has been reported [5] to be efficient for separation of uranyl ions in acidic conditions. In our earlier study [6] it was found that at pHs around 8 the SBA resin was a superior ion exchanger for uranium. The aminophosphonate resin took up uranium rather efficiently as well but its processing capacity was much lower than that of SBA resin.…”
Section: Introductionmentioning
confidence: 91%